Influencing Factors of Snow Melting and Deicing on Carbon Fiber Embedded in Bridge Decks - Yan Tan; Shuang Zheng; Henglin Xiao; JiaMing Xing (Advances in Civil Engineering)
To study the general law of the influence of embedded carbon fiber heating wires on the melting of snow and ice on bridge decks and to solve the problem of icing on large bridges in winter, relevant model tests were carried out. In this experiment, a carbon fiber heating wire was used as the heat source to make a large-scale asphalt concrete bridge deck model with a built-in carbon fiber heating wire. The effect of different heating powers, ambient temperatures, snow and ice thicknesses, and wind levels on the melting of snow and ice on bridge decks was studied. The snow-melting and ice-melting tests performed at different heating powers show that as the heating power increases within a certain range, the time required for the snow and ice layers to melt and the power consumption decrease. Under certain conditions, to ensure the rapid melting of snow and ice layers on the surface of road bridges, a heating power of 400 W/m2 is selected. At this time, the heating effect is the best, and this method is economical and practical. The snow-melting and ice-melting tests performed at different ambient temperatures and with different thicknesses of the snow and ice layers show that as the ambient temperature decreases or the thickness of the ice layer increases within a certain range while keeping the other factors constant, the time required for the snow to melt and the power consumption increase, and the power consumption is relatively large. The snow-melting test performed at different wind levels shows that with the increase in the wind level within a certain range while keeping the other factors constant, the uniformity of the overall temperature distribution on the surface of the specimen worsens, the snow-melting time increases, and the temperature rises. The rate of temperature increase decreases. Therefore, in actual engineering applications, when the wind speed is too high, the methods of manually or mechanically removing snow can increase the snow removal rate on bridge decks. Under different conditions, choosing the right heating power can effectively improve the efficiency of melting snow and ice on bridge decks. The research results of this paper provide a theoretical reference for the actual construction of bridge decks in the future.